Basic life support: a cross-sectional study of knowledge in undergraduate medical students of Maharashtra - Kawale, Suchita Narayan; Shinde, Manjusha A.; Shinde, Prashant Satawaji (International Journal Of Community Medicine And Public Health, 2020)
Background: Basic life support (BLS) is defined as medical procedures and skills that can be utilized in case of emergency to save lives. Objective was to study the knowledge of basic life support in undergraduate medical students of Maharashtra. Methods: A cross-sectional study on undergraduate medical students from first to final year MBBS in July 2018 in the Community Medicine department, Government medical college, Maharashtra. Results: Out of the total 300 students, 59.34% were females and 40.66% were males. 42% were from first MBBS, 38% from second and 20% from final MBBS. While 67% had previous training of BLS and 38% had performed CPR before. (91%) knew abbreviation of BLS (32%) students could identify location for chest compression in adults, (31%) knew the compression rate and (19%) knew about rescue breathing in infants. While (30%) and (21%) had the knowledge on depth of chest compression in adults and infants respectively. However, only (31%) and (29%) knew that the recommended chest compression to ventilation ratio in adult and infants respectively. Conclusions: The study highlights that majority of students were lacking the knowledge of basic life support. It is the need of the hour to provide BLS training to all the medical students.